Cysteine cathepsins: their role in tumor progression and recent trends in the development of imaging probes - Löser, Reik; Pietzsch, Jens (Frontiers in Chemistry, 2015)
Papain-like cysteine proteases bear an enormous potential as drug discovery targets for both infectious and systemic human diseases. The considerable progress in this field over the last two decades has also raised interest in the visualization of these enzymes in their native context, especially with regard to tumor imaging. After a short introduction to structure and general functions of human cysteine cathepsins, we highlight their importance for drug discovery and development and provide a critical update on the current state of knowledge towards their involvement in tumor progression, with a special emphasis on their role in therapy response. In accordance with a radiopharmaceutical point of view, the main focus of this review article will be the discussion of recently developed fluorescence and radiotracer-based imaging agents together with related molecular probes.